Examining the impact of company financial performance and corporate governance characteristics on CEO compensation - YANG, KE (2020)
This article mainly studies the relationship between the company's financial performance, corporate governance, and CEO compensation. We select the data of the listed companies in the UK FTSE350 in the past 10 years as our sample for research. Through data screening, we finally get the effective data of 227 companies for analysis (cash compensation model:1712 year-observations; incentive compensation model:1485 year-observations; total compensation model:1712 year-observations). In addition, this paper uses the fixed-effects model in panel data technology for analysis to avoid problems such as autocorrelation and heteroscedasticity. Empirical evidence shows that, except for CEO incentive compensation and the company's financial performance indicators are not significant, the cash compensation and total compensation are positively correlated with corporate financial performance indicators. In terms of board governance, the independence of the board is significantly positively correlated with the CEO's cash compensation, incentive compensation, and total compensation, while the size of the board and gender diversity of the board are not related to the CEO's cash compensation, incentive compensation, and total compensation. As for the governance mechanism of the compensation committee, we find that the size of the compensation committee or the independence of the compensation committee is significantly positively correlated with the CEO's incentive compensation and total compensation, but has nothing to do with cash compensation. As for the gender diversity, there is no relationship between the CEO's compensation and the gender diversity of the compensation committee. This research will help companies set and control CEO compensation better, promote the improvement of corporate governance mechanisms, and the prosperity of capital markets. Secondly, although the geographical scope of the research is limited in the UK and the research sample is limited, this research still helps companies and policymakers understand the relationship between CEO compensation and corporate financial performance and internal governance, and supplements existing research.